Insights : readings in strategic management - Hitt, Michael A. (South-Western College, 1999)
Navigating in the New competitive landscape, academy of Mgt executive. Compaq to acquire digital once an unthinkable deal, WSJ. Creating a great E-Commerce business, fortune. Read your history, Janet, Forbes. From steer to eternity, Inc. tech. Competitive advantage and internal organizational assessment...